Holy cannibalism in Deep River: eucharistic reflections on "The Case of Kiguchi" - Nelson-Hashimoto, Joshua Ryo (Literature and theology, 2025)
Endō Shūsaku's final novel Deep River weaves theological and sacramental motifs into its narrative. This article situates the novel within the Catholic literary tradition that affirms the sacramentality of artistic imagination, focusing on Eucharistic themes in the two cannibal stories of chapter 5, "The Case of Kiguchi. " By examining these narratives, it offers an alternative reading of flesh consumption that underscores the salvific potential of survivor cannibalism and human sacrifice. Eucharistic reflections on chapter 5 illuminate how sacramental grace operates in Endō's fictional world, contributing to broader conversations on the interplay between sacramental theology and literature.